Endosome and Lysosome Membrane Properties Functionally Link to γ-Secretase in Live/Intact Cells - Mei C. Q. Houser; Shane P. C. Mitchell; Priyanka Sinha; Brianna Lundin; Oksana Berezovska; Masato Maesako (Sensors, 2023)
Our unique multiplexed imaging assays employing FRET biosensors have previously detected that γ-secretase processes APP C99 primarily in late endosomes and lysosomes in live/intact neurons. Moreover we have shown that Aβ peptides are enriched in the same subcellular loci. Given that γ-secretase is integrated into the membrane bilayer and functionally links to lipid membrane properties in vitro, it is presumable that γ-secretase function correlates with endosome and lysosome membrane properties in live/intact cells. In the present study, we show using unique live-cell imaging and biochemical assays that the endo-lysosomal membrane in primary neurons is more disordered and, as a result, more permeable than in CHO cells. Interestingly, γ-secretase processivity is decreased in primary neurons, resulting in the predominant production of long Aβ42 instead of short Aβ38. In contrast, CHO cells favor Aβ38 over the Aβ42 generation. Our findings are consistent with the previous in vitro studies, demonstrating the functional interaction between lipid membrane properties and γ-secretase and provide further evidence that γ-secretase acts in late endosomes and lysosomes in live/intact cells.